(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The concept of δ-fine tagged partitions is used to simplify and unify proofs of various theorems in elementary real analysis. This paper is a continuation of the author’s project to present some properties of differentiable functions via δ-fine tagged partitions. Some basic theorems concerning Riemann integrable functions are also reproved by this concept.